Strategi Kepemimpinan Kepala Madrasah Dalam Meningkatkan Kinerja Guru - Khuliyati Khuliyati (Fakultas Ekonomi Universitas Panca Marga, 2022)
This thesis discusses the leadership strategy of madrasah principals in improving teacher performance at MTs Darul Ulum Rejosari. The leadership of the madrasah principal shows progress, which can be seen from the achievements of students at the sub-district and district levels and the number of students is increasing from year to year. The purpose of this study describes the leadership strategy of the madrasah principal in planning, in the implementation for improving, in supervising teacher performance Data sources consist of primary and secondary data. Collecting data using observation, interview and documentation techniques. Data analysis techniques were carried out by means of data reduction, data presentation, and data verification. To test the validity of the data, using triangulation techniques. The results showed that the leadership strategy of the head of the madrasa in improving teacher performance was by formulating the vision and mission of the madrasah, madrasah work programs, formulating rules, increasing discipline, providing motivation, being an example for the teacher council, conducting regular supervision, providing coaching, training activities , MGMP/STC (Subject Teacher Conference), KKG/TWG (Teacher Working Group) and seminars.